MicroRNA-9 Fine-Tunes Dendritic Cell Function by Suppressing Negative Regulators in a Cell-Type-Specific Manner - Cordeiro, Brendan; Jeon, Peter; Boukhaled, Giselle M.; Corrado, Mario; Lapohos, Orsolya; Roy, Dominic G.; Williams, Kelsey; Jones, Russell G.; Gruenheid, Samantha; Sagan, Selena M.; Krawczyk, Connie M. (Cell reports (Cambridge), 2020)
Dendritic cells, cells of the innate immune system, are found in a steady state poised to respond to activating stimuli. Once stimulated, they rapidly undergo dynamic changes in gene expression to adopt an activated phenotype capable of stimulating immune responses. We find that the microRNA miR-9 is upregulated in both bone marrow-derived DCs and conventional DC1s but not in conventional DC2s following stimulation. miR-9 expression in BMDCs and conventional DC1s promotes enhanced DC activation and function, including the ability to stimulate T cell activation and control tumor growth. We find that miR-9 regulated the expression of several negative regulators of transcription, including the transcriptional repressor Polycomb group factor 6 (Pcgf6). These findings demonstrate that miR-9 facilitates the transition of DCs from steady state to mature state by regulating the expression of several negative regulators of DC function in a cell-type-specific manner. [Display omitted] •miR-9 promotes BMDC and cDC1 function•miR-9 expression suppresses negative regulators of DC function, including PCGF6•miR-9 expressing cDC1s elicit greater antigen sensitivity in naive CD8+ T cells•miR-9 does not promote the activation or function of cDC2s Cordeiro et al. find that microRNA miR-9 promotes the activation and function of BMDCs and cDC1s but not cDC2s. miR-9 expression affects the expression of several negative regulators of DC function, including PCGF6, and promotes the ability of DCs to elicit T cell activation and control tumor growth.